Spectres photographiques : quand la photographie hante la littérature - Marie-Jeanne Zenetti (Conserveries Mémorielles)
Writers who draw their inspiration from photography (either by trying to define it or by inserting photographs into narratives) often relate it to what disappears and comes back again, to loss and haunting memories. Besides, many writers, when confronted to grief and to the return of the departed, choose to write about or with photography. From Roland Barthe’s Camera Lucida, to W. G. Sebald’s Austerlitz, Georges Rodenbach’s Bruges-la-Morte and Denis Roche’s La Disparition des lucioles, the ongoing dialogue between photography and literature raises the question of specters. Specters, which do not fully belong to one space or another, blur the limits between the world of the living and the world of the dead, they disturb the order that mourning is supposed to restore. In literary texts, photography, connecting past and present, life and death, expresses the need to give place, through writing, to what always resists to immobility, on the verge of memory.